New Zealand at the polls : the general election of 1978 - Penniman, Howard Rae. (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1980)
The series was launched in 1974 in the belief that examining particular elections in democracies with very different levels of electoral experience and economic and social development would offer scholars and policy makers a better understanding of electoral institutions and processes in all democracies.
Includes bibliographical references and index.
aia 14/05/2018
Loans
Keywords: Elections; Political parties; New Zealand